Superconductivity in Cubic A15-type V–Nb–Mo–Ir–Pt High-Entropy Alloys - Liu, Bin; Wu, Jifeng; Cui, Yanwei; Zhu, Qinqing; Xiao, Guorui; Wu, Siqi; Cao, Guanghan; Ren, Zhi (Frontiers in Physics, 2021)
We report the crystal structure and superconducting properties of new V$_{5+2x}$Nb$_{35-x}$Mo$_{35-x}$Ir$_{10}$Pt$_{15}$ high-entropy alloys (HEAs) for $x$ in the range of 0 $≤$ $x$ $≤$ 10. These HEAs are found to crystallize in a cubic A15-type structure and have a weakly coupled, fully gapped superconducting state. A maximum $T_{\rm c}$ of 5.18 K and zero-temperature upper critical field $B_{\rm c2}$(0) of 6.4 T are observed at $x$ = 0, and both quantities decrease monotonically with the increase of V content $x$. In addition, $T_{\rm c}$ shows an increase with increasing valence electron concentration from 6.4 to 6.5, which is compared with other A15-type HEA and binary superconductors.